Description of Anxiety Levels of Pregnant Women Before Emergency Caesarean Section - Naning Tutik Wijaya; Tina Mawardika (CV. Global Health Science Group, 2025)
Anxiety before an emergency cesarean section can negatively impact anesthesia, the surgical procedure, and mother infant bonding. The purpose of this study was to describe the anxiety levels of pregnant women before undergoing an emergency cesarean section. A quantitative descriptive analytic design was utilized. The population consisted of 70 pregnant women with gestational age ≥28 weeks scheduled for an emergency cesarean section. A total sampling technique was applied, involving 70 respondents (June-July 2025). The instrument used was the Hamilton Anxiety Rating Scale (HARS) questionnaire. The data analysis was presented in the form of frequency distribution since the data were categorical, describing the levels of anxiety among pregnant women undergoing emergency cesarean section. The results showed that the majority of respondents experienced moderate anxiety levels (62.8%). It can be concluded that pregnant women tend to experience moderate levels of anxiety before undergoing an emergency cesarean section.